Dynamiques des villes centre-est européennes face aux transformations politico-économiques (1961–2011) - Natalia Zdanowska (Cybergeo)
This paper examines the impact of the political and economic events of the 1990s on the demographic dynamics of Central-Eastern European cities, according to a harmonized definition of the city over time in Europe. The goal is to identify the exceptional changes that certain cities have undergone since 1961, particularly with the fall of the Berlin Wall in 1989, which signaled a paradigm shift in urban development in Central and Eastern Europe.The paper highlights a dual dynamic of cities located on the western and eastern fronts of Central-Eastern Europe. It seems that the degree of urban development of these cities is related not so much to their size as to their proximity to more advanced countries, such as Germany, Austria and Italy. These observations are in line with the theory of diffusion of innovations within complex systems and underline the importance of geographical proximity, rather than city size, in terms of urban dynamics.